Global and Diverse Markers: Challenges and Opportunities That Await Us in 2045. (December 2020) - Lipschultz, Jeremy Harris
The Post-World War II era, Journalism Quarterly pedagogical research interests, and a 21st century drive to be global and rigorous helped define the emergence of Journalism and Mass Communication Educator during a time of technological, political, social, and economic disruption. The journalism field and academic programs face continuing challenges and opportunities during the next 25 years.